Photodegradation of ethylene/propylene/polar monomers, Co-, and terpolymers. II. prepared by Ni catalyst systems - Fernandes, Susete N.; Correia, Sandra; Matos, Ines; Marques, Maria M.; Rana, Sravendra; Kumar, Bijandra; Gupta, M. K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
The copolymers of ethylene/propylene as well as their terpolymers with polar monomers were prepared by Ni-catalyst systems and their photodegradation behavior was studied by Fourier transform infrared spectroscopy. The polar monomers used to synthesize co- and terpolymers of ethylene/propylene/polar monomer were 5-hexen-1-ol, 10-undecen-1-ol, acrylamide, methylmethacrylate, acrylonitrile, and methylvinyl ketone. The morphological changes of the irradiated samples were determined by scanning electron microscopy. The photodegradation kinetics has also been studied. The surface damage caused by polychromatic irradiation (lambda >= 290 nm) at 55 degrees C in atmospheric air is presented in different micrographs. The rate of photo-oxidative degradation is very fast in terpolymers containing polar monomers as compared with copolymers and homopolymers. The morphological study of the photodegraded samples showed a very good correlation with the photodegraded results. (c) 2007 Wiley Periodicals, Inc.
Keywords: copolymerization; Ethylene; Photodegradation; polar monomers; propylene

Alkylation of benzene to cumene over mor zeolite catalysts - Vyawahare, Yogesh K.; Chumbhale, Vilas R.; Aswar, Anand S. (Revue Roumaine De Chimie, 2012)
The vapor phase alkylation of benzene to cumene (isopropyl benzene) is studied over MOR (mordenite) type zeolite at different process parameters. The reaction was also studied by adopting different methodologies (pyridine poisoning, passing of moist propylene, alkali dominant mordenite, use of coked catalyst and metal impregnated zeolite) to check the nature of product distribution and the extent of activity and selectivity to alkylated product IPB, DIPB (isopropyl benzene and diisopropyl benzene) and n-PB (n-propyl benzene). It is revealed that the adoption of different methodologies affects the activity and selectivity significantly by suppressing of alkylation / isomerisation reactions.
Keywords: Alkylation; cumene; isopropanol; MOR zeolite; propylene